Die Lebenszeugnisse Oswalds von Wolkenstein - Oswald,Schwob, Anton (Böhlau, 2013)
Until today, the death of Charles VI and Maria Theresia’s ascending the throne 1740 is seen as a major turning point in Austrian history. But now is the question of whether in different “layers” and “rooms” without doubt fundamental change between 1720 and 1780 not differentiated must be seen against the background of the concept of interface (“Sattelzeit”/Reinhart Koselleck). On the basis of the space “Viennese court”, where the change of rulers in its effects most likely can be documented, attempts from the perspective of different disciplines (the so called “Hofkünste” – literature/poetry, arts, theatre/dance, music) point out continuities and discontinuities. Der Tiroler Adelige Oswald von Wolkenstein (um 1376-1445), ein einzigartiger Exponent spätmittelalterlicher deutscher Lyrik, hat neben seinem künsterischen Werk Briefe, Urkunden und Akten hinterlassen, die seine persönliche ritterliche Karriere und das standestypische Leben seiner Zeit (soziale Vernetzungen, ökonomische Grundlagen, rechtliche Möglichkeiten) bezeugen. Die Texte wurden in ca. 40 Archiven ausgehoben, beschrieben, transkribiert und von Kommentaren eingeleitet. Mit dem 5. Bd. betreffend 1443 – 1447 ist das Werk abgeschlossen.
9783205789512
Keywords: Oswald von Wolkenstein – documents – Austrian history – Tyrolean history – lower nobility – chivalrous career – medieval life; Oswald von Wolkenstein – Urkunden; Akten – österreichische Geschichte – Geschichte Tirols – Niederadel – ritterliche Laufbahn – Leben im Mittelalter; Humanities; History; History: earliest times to present day; Early history: c 500 to c 1450/1500; Biography and True Stories; Biography: general; Biography: historical; political and military; Literature and literary studies; Poetry; Poetry by individual poets; Literature: history and criticism; Literary studies: general; Literary studies: classical; early and medieval; Law; Jurisprudence and general issues; Legal history